Birthdate of parvalbumin-neurons in the Parvafox-nucleus of the lateral hypothalamus - Bilella, Alessandro; Alvarez-Bolado, Gonzalo; Celio, Marco R. (Brain research, 2016)
The Parvafox-nucleus in the lateral hypothalamus is characterized by the presence of two distinct neural populations, the Parvalbumin (Parv) and the Foxb1-expressing ones. Foxb1-neurons are born at day 10 in the subventricular zone of the mouse mammillary region. It would be interesting to know if the subpopulation of Parv- neurons develop independently at different times and then meet the Foxb1- expressing neurons in the lateral hypothalamus, their final settling place. The aim of this study was to define the period of birth of the Parv-positive neurons using an in-vivo Bromodeoxyuridine-based method in rats. Parv-neurons are generated from embryonic day 10 to day 13, with a peak at day 12. Thus, it appears that the birthdates of the two subpopulations in these two species is similar, perhaps suggesting that they are born from the same neuroepithelial region.
Gesehen am 12.05.2020